A technique for the evaluation of failed fallopian tube ligation with metal clips. Issue 5 (1st May 2000) - Leonard, N; Mawhinney, W H B; Malcolm, A J
Abstract : The evaluation of fallopian tubes after failed tubal ligation can be difficult because conventional histopathological techniques are unable to section the metal clips when in situ. Once the clips have been removed, any evidence of tube patency is lost. This report describes a technique of embedding and sectioning that enables sections to be made while the metal clips are still in situ. This is a modification of a method first described to embed mineralised bone and involves the use of plastic embedding and a diamond saw. Using this technique, a permanent record is made of the tube location and patency.